CNN기반 딥러닝을 이용한 Kuzushiji-MNIST/49 분류의 정확도 향상을 위한 학습 방안 - 박병서(Byung-Seo Park); 이승영(Sungyoung Lee); 서영호(Young-Ho Seo) (한국정보통신학회논문지, 2020)
In this paper, we propose a deep learning training method for accurately classifying Kuzushiji-MNIST and Kuzushiji-49 datasets for ancient and medieval Japanese characters. We analyze the latest convolutional neural network networks through experiments to select the most suitable network, and then use the networks to select the number of training to classify Kuzushiji-MNIST and Kuzushiji-49 datasets. In addition, the training is conducted with high accuracy by applying learning methods such as Mixup and Random Erase. As a result of the training, the accuracy of the proposed method can be shown to be high by 99.75% for MNIST, 99.07% for Kuzushiji-MNIST, and 97.56% for Kuzushiji-49. Through this deep learning-based technology, it is thought to provide a good research base for various researchers who study East Asian and Western history, literature, and culture. 본 논문에서는 고대 및 중세 시대의 일본 문자에 대한 데이터세트인 Kuzushiji-MNIST와 Kuzushiji-49를 정확하게 분류하기 위한 딥러닝 학습 방법에 대해서 제안한다. 최신의 합성곱 신경망 네트워크들을 분석하여 가장 적합한 네트워크를 선별하고, 이 네트워크를 이용하여 Kuzushiji-MNIST와 Kuzushiji-49 데이터세트를 분류하기 위한 학습 횟수를 선정한다. 또한 Mixup과 Random Erase 등의 학습 방법을 적용하여 높은 정확도를 갖도록 학습을 진행한다. 학습 결과를 살펴보면 MNIST에 대해서는 99.75%, K-MNIST에 대해서는 99.07%, 그리고 K-49에 대해서는 97.56%의 정확도를 보임으로써 제안한 학습 방법이 높은 성능을 보일 수 있음을 증명하였다. 이와 같은 딥러닝 기반의 기술을 통해 동아시아와 서양의 역사, 문학, 그리고 문화를 연구하는 다양한 연구자들에게 좋은 연구 기반을 제공할 것으로 사료된다.